Duration of calving stages in beef cows under different housing systems - UGNIVENKO, ANATOLII; DEMCHUK, STEPAN; NOSEVYCH, DMYTRO; BONDARENKO, GENNADII (The Indian Journal of Animal Sciences, 2021)
The goal of research was to analyze the calving process and duration of calving stages in beef cows under moderately continental climate conditions and various systems of housing and feeding. Duration of calving stages have been studied in Ukrainian Beef breed cows under four types of housing conditions: tie-stall housing before and during calving; free stall housing before calving with calving in the calving pens; housing in the outside paddocks and calving in the calving pens; keeping cows on pasture before and during calving. It has been proved that under tie-stall housing system of cows, the preparatory stage is the shortest, and period of withdrawal of the fetus and period of placenta discharge are the most prolonged. When cows were kept on pastures, the preparatory stage labour lasted for or a longer time, but the withdrawal of the fetus and the after-labour period were the shortest. When close-up cows stayed in free-stall barns and calved in the pens or calving chutes, the stages of labour went faster as compared to calving in the outside paddocks, but longer as compared to calving on pasture. Movement of cows from outside paddocks into calving pens increases variability in the duration of parturition, due to the stress of changing location.